A Comprehensive Examination of Artificial Intelligence in the Field of Education - Khatoon, Umme Thayyiba; Madkhali, Rafeef Ahmed (Indian Journal of Computer Science, 2023)
The objective of this study was to evaluate the influence of Artificial Intelligence (AI) on the field of education. Based on an initial analysis, this study focused on the use and impact of Artificial Intelligence (AI) in the domains of administration, instruction, and learning. The study was guided by a narrative and framework for evaluating AI. The study effectively employed a qualitative research approach, utilizing literature review as a research design and approach to successfully achieve the study's objectives. Artificial Intelligence (AI) encompasses a scholarly discipline focussed on the exploration and subsequent advancements in Computer Science, leading to the creation of intelligent systems, robots, and other artifacts that exhibit cognitive powers, learning capacities, adaptability, and decision-making prowess akin to human intelligence. The research determined that Artificial Intelligence (AI) has been widely embraced and implemented in the field of education, specifically by educational institutions, in many manifestations. Artificial intelligence (AI) was initially developed in the form of computer technologies and their associated applications. Over time, it has evolved to include web-based and online intelligent education systems. Furthermore, the integration of embedded computer systems, along with other technologies has facilitated the use of humanoid robots and web-based chatbots to independently or collaboratively perform instructors' duties and functions. Through the use of these platforms, educators have been able to execute various administrative tasks with greater effectiveness and efficiency. These tasks include the review and evaluation of students' assignments, resulting in an enhanced quality of their instructional endeavours. However, due to the utilization of Machine Learning and adaptability, the educational systems have been able to adjust and personalize curriculum and content according to the specific needs of students. This has resulted in increased adoption and retention rates, thus enhancing the entire learning experience and quality for learners.